Greve dos trabalhadores da educação da rede estadual de Minas Gerais em 2011: experiências e sujeitos - Edgard Leite de Oliveira (2016)
The thesis has as objective research on the strike of workers of Education of the State of Minas Gerais Network in 2011. It features the look of some participating employees, their analyzes and reflections on this process.History, memory and experience of the movement ofteachers of the state of Minas Gerais from the street movements in 2011, political activism proposals. Confrontation to the organization model and privatization of state in Minas Gerais, called Management Shock.